Analysis of Determining Public Speaking Skill Levels of Junior High School Students Using the TOPSIS Method at Phatnawitya School, Yala, Thailand - Zaky Soleh Wirawan; Mhd. Basri (Journal of General Education and Humanities, 2026)
Evaluating junior high school students' public speaking skills often faces the challenge of subjectivity, especially in international schools where manual assessment lacks mathematical rigor. This study applied the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method with manual calculations to objectively rank 28 students from Phatnawitya School, Yala, Thailand, based on seven Canva presentation criteria: Eye Contact, Body Language, Poise, Subject Knowledge, Fluency, Pronunciation, and Comprehension. Using a descriptive quantitative approach, purposive sampling targeted one top-tier class as the sample population. Teachers' Excel assessment data were analyzed using TOPSIS through decision matrix formation, normalization, weighted normalization, ideal solution determination, distance calculation, and preference assessment. The results showed that Salsabil Hayitahe ranked first (V=0.65) and Muhammadsharif Seng last (V=0.36), proving the effectiveness of TOPSIS in providing transparent, bias-free ranking. The conclusions confirm the suitability of manual TOPSIS for multi-criteria educational evaluation, without software dependence, and recommend its wider application across various classes.